Is the Australian nursing workforce ready to embrace prescribing under supervision? A cross‐sectional survey - Fox, Amanda; Crawford‐Williams, Fiona; Ria, Joseph; Lynda, Cardiff; Debra, Thoms; Patsy, Yates; Lisa, Nissen; Chan, Raymond Javan (Journal of advanced nursing, 2022)
Aim The aim was to explore nurses' preparedness to expand their practice to prescribe medicines under a supervision model. Design This was a cross‐sectional study. Methods A convenience sample of Australian nurses recruited from memberships of State‐based Nursing and Midwifery Unions and professional bodies from diverse care settings. Nurses undertook an online researcher‐constructed survey between March and July 2021 to identify current prescribing practices, motivations for undertaking education in prescribing and perceived barriers to implementation of nurse prescribing under supervision. Data related to demographics, nursing experience and barriers to becoming a prescriber were analysed descriptively. Logistic regression was used to model nursing experience variables with desire to become a prescriber. Results A total of 4424 nurses participated with the majority (n = 3645, 82%) reporting they were highly likely to expand their practice to prescribe medicines under supervision. The main motivations to prescribe were to enhance patient care and job satisfaction. Nurses were more likely to want to prescribe if they had <10 years experience (95% CI = 0.3–0.5, p < 0.001), held a bachelor's degree (95% CI = 1.3–2.2, p < 0.001) or higher qualification (95% CI = 1.8–2.9, p < 0.001). Most reported lack of acknowledgement of increased responsibility and workloads (n = 4098, 93%), and insufficient organizational support (n = 4197, 95%) may prevent uptake of nurse prescribing. Conclusions Most Australian nurses demonstrated their preparedness to embrace the role of prescribing under supervision. The perceived barriers identified in this study can inform future implementation of this expanded nursing role. Impact The Nursing and Midwifery Board of Australia has proposed a standard of practice to enable nurses to prescribe under supervision. Models of nurse prescribing are being considered globally to address population needs. Successful adoption of this practice is dependent on aspects such as key personnel's acceptance of the initiative. The workforce readiness and barriers highlighted in this study can inform implementation at policy and organizational levels.